OPTIMALIZATION OF THE ROLE AND FUNCTIONS OF THE LOCAL PROPERTY BOARD IN THE SUPERVISION OF THE USE OF LIMITED LANDS IN THE CABITATES OF THE NATIONS RELATED TO THE LAW NUMBER 17 OF 2014 (Case Study at the People's Representative Council of Karawang Distri - Norma Indah Nur Fitrianingsih; Muhamad Gary Gagarin Akbar; Sartika Dewi (Justisi: Jurnal Ilmu Hukum, 2023)
Law Number 9 of 2015 concerning the Second Amendment to Law Number 23 of 2014 concerning Regional Government is used as one of the formal sources in Indonesia. So that every government activity carried out must be in accordance with these regulations. The phenomenon that occurs in Karawang Regency is that there is still a lack of supervision carried out by the Karawang DPRD so this research wants to discuss the role and function of DPRD supervision in supervising the regional budget and what obstacles are experienced in carrying out this supervision. The purpose of this study is to find out what kind of supervision is carried out by the DPRD of Karawang Regency in supervising the regional budget. This research is a type of qualitative research that uses a normative juridical approach, namely by going through library materials and the results of direct interviews in the field. The results of his research are that the Karawang DPRD has not been optimal in overseeing the use of the budget, this can be proven from the findings of the BPK which continues to increase every year and the obstacles experienced by the DPRD, namely technical constraints.